Functionalized Silver Nanoparticles as Colorimetric and Fluorimetric Sensor for Environmentally Toxic Mercury Ions: An Overview - Pomal, Nandan C.; Bhatt, Keyur D.; Modi, Krunal M.; Desai, Ajay L.; Patel, Nihal P.; Kongor, Anita; Kolivoška, Viliam (Journal of fluorescence, 2021)
Nanoscience is a multifaceted field which encompasses metal nanoparticles (MNPs) having novel and size-related optical properties significantly different from the bulk level as well as at the atomic level. Amongst noble MNPs, the silver nanoparticles (AgNPs) have unique properties for metal interaction. Presently, there have been expedite reports which are taken under the review in virtue of sensing the mercury ions in aqueous media. Mercury dissemination in various forms contaminates the ecosystem. Globally mercury is ranked as the most toxic element and an urgent threat to humans since it causes major health issues. Employing MNPs, especially AgNPs for the detection of mercury ions is the economic, handy and apt method in contrast to time-consuming methods that use expensive instrumentations. The review highlights a study of colorimetric and fluorimetric detection of the level of Hg (II) ions in aqueous media selectively with high sensitivity in different courses of conditions using AgNPs synthesized by various approaches. Graphical abstract